Bioelectronics on Mammalian Collagen. (15th July 2020) - Moreno, Salvador; Keshtkar, Javad; Rodriguez‐Davila, Rodolfo Antonio; Bazaid, Arwa; Ibrahim, Hossam; Rodriguez, Brian J.; Quevedo‐Lopez, Manuel Angel; Minary‐Jolandan, Majid
Abstract: Collagen has emerged as an attractive bioelectronics substrate candidate, given its biological origins as a structural protein found in organisms. Substrates for implantable electronics should be biocompatible and have similar mechanical properties to implant target tissues. Furthermore, the characteristic amino acid sequences in collagen promote cell adhesion, migration, and proliferation, all of which are advantageous when compared to commonly explored cellulose and silk. However, denaturation temperature and swelling in water/vacuum have been fundamental barriers to device fabrication on collagen. It is here described how these problems can be avoided for the fabrication of semiconductor devices on collagen. Transfer printing using a sacrificial layer of germanium oxide is used to fabricate capacitors, transistors, and an integrated inverter transistor circuits on the collagen substrate. The mobility and threshold voltage of the transistors on collagen show only ≈41% and ≈22% drop compared to the ones on rigid silicon substrate. The enzymatic digestion and swelling ratio of collagen can be decreased by 80% and 175%, respectively, via glutaraldehyde cross‐linking, while mechanical stiffness increases by more than 270%. This work demonstrates how collagen can be used as a bioelectronics substrate with tunable properties, thereby expanding its application range from transient to more permanent implantable electronics. Abstract : Manufacturing bioelectronics on structural protein collagen requires a novel strategy to overcome material limitations. Transfer printing of electronics using a sacrificial layer of germanium oxide is demonstrated to fabricate devices including capacitors, transistors, and inverters on collagen for the first time. Devices built on collagen films are shown to be programmatically enhanced to resist enzymatic digestion using glutaraldehyde.